(untitled) (Homoeopathy for All, 2024)
Crystal agglomerates that grow in the urinary tract and can occasionally pass through it cause a frequent urological condition known as kidney stones (KS). Greek term nephros means kidney, uro means urinary and lithos means stone, are also used to refer to it as nephrolithiasis or urolithiasis. In other system of medicine, there are various methods of treatment including surgery with chances of recurrence. Hence, there is a need to develop a simple cost effective, painless line of treatment, which not only removes the calculi/ calculi’s, but also helps in removing the tendency for recurrence of calculi formation. Homoeopathy offers good number of remedies for removing calculi and tendency for recurrence of calculi. Now a day’s homoeopathy is playing a crucial role in the management of renal calculi and this helping in treating the problem without surgery and in avoiding recurrence of the disease with the use of homoeopathic medicine.